1989
DOI: 10.1093/oxfordjournals.aje.a115134
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Prevalence of Non-Insulin-Dependent Diabetes Mellitus in a Biethnic Colorado Population

Abstract: The San Luis Valley Diabetes Study was undertaken to determine the prevalence, risk factors, and complications of non-insulin-dependent diabetes mellitus in Hispanics and Anglos (non-Hispanic whites), using a geographically based case-control design. The study was conducted in two southern Colorado counties that include 43.6% Hispanic and 54.9% Anglo persons. Medical practice records were reviewed to identify medically diagnosed diabetics. Controls without diabetes were identified by a two-stage random sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
122
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(127 citation statements)
references
References 0 publications
5
122
0
Order By: Relevance
“…Clinical centres in Oakland and Los Angeles, California, studied non-Hispanic whites and African Americans recruited from Kaiser Permanente, a nonprofit health maintenance organization. Clinical centres in San Antonio, Texas, and San Luis Valley, Colorado, studied non-Hispanic whites and Hispanics recruited from two ongoing population-based studies (the San Antonio Heart Study [20] and the San Luis Valley Diabetes Study [21]). Recruitment was tailored to yield approximately equal numbers of participants by ethnicity, sex, and glucose tolerance categories [Type II diabetes, impaired glucose tolerance (IGT) and normal glucose tolerance].…”
Section: Methodsmentioning
confidence: 99%
“…Clinical centres in Oakland and Los Angeles, California, studied non-Hispanic whites and African Americans recruited from Kaiser Permanente, a nonprofit health maintenance organization. Clinical centres in San Antonio, Texas, and San Luis Valley, Colorado, studied non-Hispanic whites and Hispanics recruited from two ongoing population-based studies (the San Antonio Heart Study [20] and the San Luis Valley Diabetes Study [21]). Recruitment was tailored to yield approximately equal numbers of participants by ethnicity, sex, and glucose tolerance categories [Type II diabetes, impaired glucose tolerance (IGT) and normal glucose tolerance].…”
Section: Methodsmentioning
confidence: 99%
“…1822 Because Latino immigrants constitute the largest proportion of immigrants to the United States by far, there has been interest in understanding whether acculturation to US lifestyles contributes to their heightened diabetes risk. The evidence on whether the risk of type 2 diabetes in Latino immigrant populations increases with greater time in the United States or acculturation, however, is mixed.…”
mentioning
confidence: 99%
“…
Numerous studies have shown that Mexican Americans have an increased prevalence [1][2][3][4] and incidence [5] of non-insulin-dependent diabetes mellitus (NIDDM) relative to non-Hispanic whites. The Mexican American population is characterized by increased adiposity [1][2][3][4]6], a more centralized distribution of body fat [6,7], hyperinsulinaemia [8][9][10] and insulin resistance [11,12].

Metabolic factors have been shown to be important risk factors for the development of NIDDM.

…”
mentioning
confidence: 99%
“…The Mexican American population is characterized by increased adiposity [1][2][3][4]6], a more centralized distribution of body fat [6,7], hyperinsulinaemia [8][9][10] and insulin resistance [11,12].Metabolic factors have been shown to be important risk factors for the development of NIDDM. Both insulin resistance [13,14] and hyperinsulinaemia [13,[15][16][17][18][19] have been shown to predict NIDDM.…”
mentioning
confidence: 99%
See 1 more Smart Citation